A formação Serra Alta, Permiano, no centro-leste do Estado de São Paulo, Bacia do Paraná, Brasil - Warren, Lucas Veríssimo [UNESP]; Assine, Mario Luis [UNESP]; Simões, Marcello Guimarães [UNESP]; Riccomini, Claudio; Anelli, Luís Eduardo (Sociedade Brasileira de Geologia, 2015)
The delimitation and mapping of the Serra Alta Formation in the São Paulo State, Brazil, has always been a focus of controversy in the Brazilian geological community. Despite its large extension in subsurface, which may be comparable to the Irati Formation, the Serra Alta Formation still needs more detailed studies on its stratigraphic position, fossil content, depositional systems and age. In the east-central portion of the São Paulo State, the Serra Alta Formation overlies the Irati Formation and is predominantly composed of dark grey pelitic facies. The unit is mapped from the southern boundary of the São Paulo State to the Gibóia Dome, located in the county of Rio das Pedras. In this place, the Serra Alta and Teresina formations are replaced by the red colored pelites of the Corumbataí Formation, unit that extends to north beyond the state boundaries and may be considered correlated to these units. In this work, we present columnar sections and describe the contacts of the Serra Alta Formation with vertically adjacent Permian units. We also present the detailed facies analysis, in order to characterize the depositional system. The investigation of subsurface profiles also enabled a better understanding of the architectural patterns of the succession, helping to determine its real distribution and stratigraphic position in the central-south of São Paulo State. The integration of the data allowed identifying a particular transgressive stacking pattern, contributing to detail the late Permian regressive cycle in the Paraná Basin.

A individualização e o mapeamento da Formação Serra Alta no Estado de São Paulo sempre foi motivo de controvérsia na comunidade geológica. Apesar de apresentar extensão comparável à Formação Irati em subsuperfície, a unidade ainda carece de estudos mais acurados acerca de seu posicionamento estratigráfico, conteúdo fossilífero, sistema deposicional e idade. Na região centro-leste do Estado de São Paulo, a Formação Serra Alta sucede estratigraficamente a Formação Irati, sendo constituída por depósitos pelíticos cinza escuros. A unidade é mapeada desde o limite sul do estado até o Domo de Gibóia, no Município de Rio das Pedras. Neste local, as formações Serra Alta e Teresina são substituídas pelos depósitos pelíticos da Formação Corumbataí, que se estende para norte, além do limite do Estado de São Paulo, e pode ser considerada unidade correlata a estas. Neste estudo, são apresentadas seções colunares e caracterizados os contatos da Formação Serra Alta com as formações permianas verticalmente contíguas. É apresentada também detalhada análise de fácies, com a finalidade de caracterizar o sistema deposicional. A análise de perfis de sondagem possibilitou também melhor compreensão dos padrões arquiteturais da Formação Serra Alta, auxiliando na determinação de sua real distribuição e posição estratigráfica na porção centro-sul do estado. A integração das informações obtidas permitiu identificar tendências de empilhamento transgressivo particulares, contribuindo para o detalhamento da sucessão predominantemente regressiva em que se depositaram as unidades permianas da Bacia do Paraná.
The Serra Alta formation, Permian, in the central-eastern portion of São Paulo State, Paraná Basin, Brazil
Keywords: Serra Alta Formation; Sedimentology; Stratigraphy; Paleontology; Permian; Paraná Basin; Formação Serra Alta; Sedimentologia; Estratigrafia; Paleontologia; Permiano; Bacia do Paraná